2017
DOI: 10.1038/s41598-017-01634-2
|View full text |Cite
|
Sign up to set email alerts
|

Policing the legume-Rhizobium symbiosis: a critical test of partner choice

Abstract: In legume-Rhizobium symbioses, specialised soil bacteria fix atmospheric nitrogen in return for carbon. However, ineffective strains can arise, making discrimination essential. Discrimination can occur via partner choice, where legumes prevent ineffective strains from entering, or via sanctioning, where plants provide fewer resources. Several studies have inferred that legumes exercise partner choice, but the rhizobia compared were not otherwise isogenic. To test when and how plants discriminate ineffective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 66 publications
7
96
0
1
Order By: Relevance
“…Our results support a novel function for nodules, highlighting a clear benefit for the bacteria, regarding their diversification and evolution through conjugative transfer. Nodulation is usually a specific process, where certain bacteria interact with certain legumes (Gage, 2004;Popp and Ott, 2011;Westhoek et al, 2017) however, nodules have been shown to contain other endogenous bacteria, including diverse rhizobial and non-rhizobial genera, such as Agrobacterium, Enterobacter, Chryseobacterium, Sphingobacterium, Actinobacteria and unclassified Enterobacteriaceae (Dudeja et al, 2012;Mora et al, 2014;De Meyer et al, 2015;Leite et al, 2016;Lu et al, 2017). Nodules contain a high number of bacteria, about 10 9 (Downie, 2014); even if the most abundant are rhizobia, 10 5 -10 8 may belong to other genera (Sturz et al, 1997;Martínez-Hidalgo and Hirsch, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support a novel function for nodules, highlighting a clear benefit for the bacteria, regarding their diversification and evolution through conjugative transfer. Nodulation is usually a specific process, where certain bacteria interact with certain legumes (Gage, 2004;Popp and Ott, 2011;Westhoek et al, 2017) however, nodules have been shown to contain other endogenous bacteria, including diverse rhizobial and non-rhizobial genera, such as Agrobacterium, Enterobacter, Chryseobacterium, Sphingobacterium, Actinobacteria and unclassified Enterobacteriaceae (Dudeja et al, 2012;Mora et al, 2014;De Meyer et al, 2015;Leite et al, 2016;Lu et al, 2017). Nodules contain a high number of bacteria, about 10 9 (Downie, 2014); even if the most abundant are rhizobia, 10 5 -10 8 may belong to other genera (Sturz et al, 1997;Martínez-Hidalgo and Hirsch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria trapped in the curled root hairs penetrate the plant through the infection thread and then are released into the nodules, where they differentiate into nitrogen-fixing bacteroids (Gage, 2004;Quinto et al, 2014). The general view has been that the plant benefits from this association by receiving fixed nitrogen, while the bacteria receive other nutrients, mainly carbon sources (Haag et al, 2013;Westhoek et al, 2017). Using cultivation and genomic approaches, other plant growth promoting bacteria have been shown to be present in the nodules, indicating that bacteria lacking the genes required for nodulation may enter the nodules, probably hitchhiking among the nodulating bacteria (Dudeja et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…strain ORS285 ΔbclA nodule bacteria, the high activity of the CBB cycle might reflect this intermediate stage, after oxygen levels have dropped, as discussed above, but before nitrogen fixation. This also implies that the plant is not sanctioning the absence of effective nitrogen fixation by stopping carbon supply to the bacterium, although sanctions have been shown to be applicable to noncooperative rhizobia in other legume-rhizobium systems (47,48).…”
Section: Fig 3 Legend (Continued)mentioning
confidence: 99%
“…Результаты диаллельных скрещиваний показали, что наследуемость признака Hop у люцерны хмелевидной (Medicago lupulina) достаточно высока для того, чтобы в растительных популяциях происходил отбор на усиление этого признака [32]. Однако в большинстве симбио тических систем связь Hop и СЭ не выявляется: при смешанном инфицировании растения с равным успехом инокулируются фиксирующими и не фиксирующими N 2 -штаммами ризобий [33]. Несмотря на это, [34].…”
Section: контроль эффективности симбиоза растениемunclassified